MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH DALAM PENINGKATAN KINERJA GURU DI SDN DERMO II BANGIL - Dhatul Hikmah; Ahmad Thohirin; M. Furqon Wahyudi (STKIP Pesisir Selatan, 2026)
Objective: This study aims to explore how the principal’s managerial leadership contributes to improving teacher performance at SDN Dermo II Bangil. Using a qualitative case study approach, the research investigates the everyday practices, interactions, and decision-making patterns demonstrated by the school principal in leading learning and managing teachers. Data were collected through in-depth semi-structured interviews with three teachers, participatory observation of school activities, and documentation analysis of supervisory reports and school records. The thematic analysis revealed three core themes: (1) inclusive and communicative leadership that fosters trust and collaborative decision-making; (2) adaptive academic supervision characterized by dialogic feedback, emotional support, and constructive guidance; and (3) strengthened teacher motivation, discipline, and instructional innovation as a direct impact of the principal’s exemplary behavior and professional support. These findings highlight the pivotal role of relational and adaptive leadership in shaping teacher professionalism within the social and cultural context of elementary schools. The study contributes to leadership theory by emphasizing the emotional and interpersonal dimensions of transformational leadership in basic education. Practically, the results suggest the need for structured principal training focused on communication and collaborative supervision.